A simple, self-referenced, intensity-based optical fibre sensor for temperature measurements - Silva, Ricardo M. (2019)
A sensing configuration based on an intensity optical fibre sensor for temperature measurement is reported. Two sensing heads, with identical geometrical configuration, connected in series are implemented. Each sensing head is placed between two fibre Bragg gratings (FBGs), being able to provide a self-referenced measurement, and thus eliminate errors that may arise from undesired intensity fluctuations in the configuration. The first FBG, placed before the aluminium tube, acts as the reference FBG, while the second FBG, placed after the aluminium tube, acts as the signal FBG. It is observed that the amplitude of the signal FBG decays when temperature increases, due to the increase of the ferrules' gap and as result of the material thermal expansion. The temperature response has a behaviour that corresponds to a polynomial fit of third order. The crosstalk between the two sensing heads in series is analysed. The temperature sensitivities obtained in the intervals regions of [36, 48.5] °C and [64, 85] °C are 2.67×10-3 °C-1 and 1.74×10-4 °C-1, respectively. Ten sensing heads with this configuration can be multiplexed in series network topology.